2016
DOI: 10.3390/ijms17101705
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Receptor Excision Circle (TREC) Monitoring after Allogeneic Stem Cell Transplantation; a Predictive Marker for Complications and Clinical Outcome

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is a well-established treatment modality for a variety of malignant diseases as well as for inborn errors of the metabolism or immune system. Regardless of disease origin, good clinical effects are dependent on proper immune reconstitution. T cells are responsible for both the beneficial graft-versus-leukemia (GVL) effect against malignant cells and protection against infections. The immune recovery of T cells relies initially on peripheral expansion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 107 publications
0
18
0
2
Order By: Relevance
“…Previous reports have shown that assessing recipient thymic and bone marrow function can predict HSCT outcome [4,5]. A practical method for monitoring thymopoiesis and B cell reconstitution after transplantation is the quantification of T cell receptor excision circles (TRECs) generated during T cell receptor gene rearrangement and kappa-deleting recombination excision circles (KRECs) generated during Ig light chain rearrangement, respectively [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that assessing recipient thymic and bone marrow function can predict HSCT outcome [4,5]. A practical method for monitoring thymopoiesis and B cell reconstitution after transplantation is the quantification of T cell receptor excision circles (TRECs) generated during T cell receptor gene rearrangement and kappa-deleting recombination excision circles (KRECs) generated during Ig light chain rearrangement, respectively [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical situations associated with aging have been described as possible causes of impaired thymic function, including changes in growth factor and cytokine expression, low hormone production, and bone marrow loss ( 7 , 8 ). TREC quantification has been shown in various studies to be more reliable for evaluation of thymic function ( 9 16 ). A series of observations on TREC dynamics during human immunodeficiency virus (HIV) infection and treatment and in autologous and allogeneic hematopoietic stem cell transplantation (HSCT) confirmed the usefulness of TREC analysis as a quantitative marker for thymic function.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors injuring the thymus can delay the recovery of thymopoiesis after HSCT including: increasing age of the recipient, occurrence and grade of acute or chronic graft versus host disease (aGvHD, cGvHD), intensity of conditioning, source of stem cells, infections in the transplant period (especially CMV reactivation) or previous treatment of the underlying disease (malignant or non-malignant) [15,17]. Median age of the patients at the time of HSCT was 7.7 years (range 6 months to 19.5 years).…”
Section: Introductionmentioning
confidence: 99%